Unravelling the Sequence Stratigraphy Impact on Coal Geometry of M2 Member, Muara Enim Formation - Hibatullah, Kevin Nabil; Setiawan, Budhi; Rochmana, Yogie Zulkurnia; Wicaksono, M Dwiki Satrio (UIR PRESS, 2026)
Sequence stratigraphy involves studying a series of rock layers deposited during a full change cycle in accommodation or sediment supply, bounded by subaerial unconformities and marine correlative conformities. This study aims to identify the stratigraphic sequence that controls the coal accumulation models and their influence on the coal geometry. The research methodology includes geological mapping, analysis of geophysical logs (gamma-ray and short density), and core log analysis. The data were analyzed, combined, interpreted, and simulated to create a model of coal accumulation and geometry. The M2 Member of the Muara Enim Formation comprises six lithofacies, as determined by analyzing four drill holes. The M2 Member of the Muara Enim Formation exhibits four depositional environments (crevasse splay, mire/swamp, mudflat, lagoon, and tidal/mouth/distal bar) and three facies associated with the fluvial delta–tidal plain facies (fluvial dominated upper delta plain, tide-dominated lower delta plain, and marginal tidal plain and lagoon). This research identified four system tracts, namely TST-1, HST-1, TST-2, and HST-2. TST-1 and TST-2 show continuous coal deposition, inclined to steeply inclined, interspersed, and characterized by the presence of three layers of clay bands. Similarly, HST-1 and HST-2 exhibit continuous coal deposition with gentle to steep inclined and interspersed, ranging from moderately thick to very thick, and containing one to five layers of clay bands. The tectonic activity after deposition caused the deposited coal to deform. The findings of this study contributed to guiding the exploration of coal seams in the South Sumatra Basin and Muara Enim Formation, in particular.